Teacher's Creativity in Providing Reinforcement to Enhance Students' Learning Independence - Rini Amelia Siagian; Arlina Arlina (Jurnal Pendidikan (Teori dan Praktik), 2025)
This study aims to explore teachers' creativity in the learning process through providing reinforcement to students and the impact resulting from the use of reinforcement. This is carried out because low motivation and initiative in student learning were found, thus requiring teacher creativity to address it. This study uses a qualitative approach with a descriptive phenomenological method. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model through stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have applied reinforcement creatively through storytelling methods, verbal and symbolic reinforcement, as well as assigning responsibilities oriented towards Islamic moral values. Teachers do not merely deliver material, but also serve as role models in attitude and behavior, so that the reinforcement given is not purely instructional, but also touches the emotional and spiritual aspects of students. This strategy is effective in fostering independent learning, marked by an increase in students' courage to ask questions, answer, and take the initiative to learn independently. These findings reinforce that teachers' creativity in providing reinforcement plays an important role in shaping students' character and intrinsic motivation in Akidah Akhlak learning.